Review of Contact Lens–Related Complications. (November 2018) - Lim, Chris H. L.; Stapleton, Fiona; Mehta, Jodhbir S.
Abstract : Abstract: The purpose of this article is to provide a review of existing literature describing complications with contemporary contact lenses and their management. It is envisioned that this will serve as a useful summary of noninfectious and infectious complications associated with contact lens wear.